MENEJEMEN SUMBER DAYA MANUSIA DI PERPUSTAKAAN - S. Komarudin, Yooke Tjuparmah; Dewi, Laksmi (Universitas Pendidikan Indonesia, 2012)
The era in which the exstense of ICT brings with it enlightenment in every aspect of life changes of paradigms in libraries exists. The change includes a transfer in system – from conventional type of services to ICT-based services with some orientation for the sake of users’ needs. The innovations taking place in libraries are influenced by 10 issues: